Designing A Digital-Based Surveillance Information System Prototype for Epidemiological Investigation of Avian Influenza (H5N1) In Bali Province - I Gusti Ngurah Agung Surya Pratama; Putu Putri Agustini; I Dewa Agung Ayu Ari Shinta Dewi; I Made Subrata; Ngakan Putu Anom Harjana; Sang Gede Purnama; Romy Muhammad Dary Mufa (Journal of Public Health Sciences, 2026)
Avian Influenza (AI) is an infectious disease that can attack birds and humans caused by a virus. Until April 2023, the number of human victims infected with AI disease in the world reached 874 people (confirmed AI cases), with 458 of them dying (CFR = 52%). Health Surveillance is a systematic and continuous observation activity of data and information about the incidence of disease or health problems and conditions that influence the increase and transmission of disease or health problems. The aim of the research is to design a digital-based AI epidemiological surveillance system in Bali Province. The research design used in this research is a research and development (R&D) approach with a prototyping development model. Acceptance tests were carried out on 130 surveillance officers with the PSSUQ questionnaire. The results obtained were in the form of a prototype AI epidemiological investigation information system application with acceptance test results regarding system quality (2.37), information quality (2.43), and the overall system (2.37) showing very good results. Meanwhile, acceptance of the quality of the design or appearance of the prototype is in the good category (2.37). This value is classified based on the norm scale of the PSSUQ questionnaire. Conclusion: Therefore, this AI epidemiological investigation surveillance information system is worthy of further development.